Shift Restrictions and Semiparametric Estimation in Ordered Response Models - Klein, Roger W.; Sherman, Robert P. (Econometrica, 2002)
We develop a $\sqrt{n}\text{-}\text{consistent}$ and asymptotically normal estimator of the parameters (regression coefficients and threshold points) of a semiparametric ordered response model under the assumption of independence of errors and regressors. The independence assumption implies shift restrictions allowing identification of threshold points up to location and scale. The estimator is useful in various applications, particularly in new product demand forecasting from survey data subject to systematic misreporting. We apply the estimator to assess exaggeration bias in survey data on demand for a new telecommunications service.